Diseño de una Plataforma Tecnológica para asegurar la Continuidad de Negocios - Chacón-Rodríguez, Oscar (My University, 2008)
Now days, companies are increasingly dependent on information technology (IT) in their daily activities. Dependency ranges from simple email service, up videoconferencing services and customer relationship management systems (CRM by its acronym in English). Dependency has reached levels so complex that if the IT services stop even for a few hours, the economic losses are so large they can carry a company into bankruptcy. This is especially true to financial nature institutions, for whom access to information of financial statements of their clients is vital and to lose this information is completely unacceptable because the legal obligations financial institutions have with their clients. The importance of IT services of a company been available 24 hours a day, 365 days a year is indisputable and this is what justifies the existence of a business continuity plan that will ensure a company keeps its IT services up and running in the event of a disaster happens in their main datacenter.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2008.
Keywords: Datos; Servidores; Software; Ancho de banda; Controladores; Sincronización; Almacenamiento; Fuentes de poder; Estrategia